2018
DOI: 10.1029/2018gl077352
|View full text |Cite
|
Sign up to set email alerts
|

Methane Ebullition From Subtropical Peat: Testing an Ebullition Model Reveals the Importance of Pore Structure

Abstract: The role of subtropical peatlands as a source for methane gas is not well understood, partly due to uncertainties surrounding environmental controls on gas ebullition patterns. Past studies have pointed to an array of environmental factors controlling ebullition, although we have found that ebullition patterns can be replicated by a model considering only physical parameters of the peat matrix. Here we tested a computer model for gas ebullition and storage against a natural system for the first time, using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…While some studies found positive relationships between gas storage and release (Liu et al 2020), others did not see any correlation between CH 4 content in the sediment and ebullition rates in lakes (Martinez and Anderson 2013). Contradictory findings were also obtained concerning gas storage and sediment properties; while high gas storage was associated with high porosity sediments and peat in some studies (Martinez and Anderson 2013; Wright et al 2018), others found low‐porosity, sandy sediment to store and retain more gas (Ramirez et al 2015). In some cases, ebullition was found to correlate positively with sediment sand content (Amos and Mayer 2006; Martinez and Anderson 2013).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While some studies found positive relationships between gas storage and release (Liu et al 2020), others did not see any correlation between CH 4 content in the sediment and ebullition rates in lakes (Martinez and Anderson 2013). Contradictory findings were also obtained concerning gas storage and sediment properties; while high gas storage was associated with high porosity sediments and peat in some studies (Martinez and Anderson 2013; Wright et al 2018), others found low‐porosity, sandy sediment to store and retain more gas (Ramirez et al 2015). In some cases, ebullition was found to correlate positively with sediment sand content (Amos and Mayer 2006; Martinez and Anderson 2013).…”
Section: Discussionmentioning
confidence: 93%
“…The peat matrix and physical peat structure were found to play a crucial role in the accumulation and release of CH 4 bubbles (Wright et al 2018). While some studies found positive relationships between gas storage and release (Liu et al 2020), others did not see any correlation between CH 4 content in the sediment and ebullition rates in lakes (Martinez and Anderson 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For in situ CH 4 emission rate estimation, we applied a modified gas trap method in the field and estimated gas fluxes from weekly to biweekly volumes of biogenic gas releases (Wright et al, 2018). We mounted traps in wooden platforms with pilings driven to the mineral soil to avoid soil disturbance during data collection.…”
Section: In Situ Data Collection Approachmentioning
confidence: 99%
“…Studies of CH 4 in wetlands concentrate on CH 4 emission estimation (Bartlett & Harriss, 1993;Wang et al, 1996), mechanisms of production and consumption (Segers, 1998), and its role in the global climate system (Dean et al, 2018). Traditionally, CH 4 flux data are acquired through time-consuming and labor-intensive point-based approaches at 1-m scale like chambers (e.g., Morin et al, 2017;Whiting & Chanton, 2001) and recent gas traps fitted with time-lapse cameras (Comas & Wright, 2012;Wright et al, 2018), or from eddy covariance towers at 100-to 1,000-m scale (e.g., Morin et al, 2017). In situ methods are spatially constrained and difficult in remote locations or harsh environments like wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…Physical properties and structure of the peat matrix are also a critical control dictating the spatial and temporal distribution of biogenic gases in peat soils (Wright et al, 2018). Biogenic gases (e.g., CH 4 ) generated and accumulated within the peat column can significantly decrease K (Baird & Waldron, 2003; Reynolds et al, 1992).…”
Section: Introductionmentioning
confidence: 99%